A Rare Occurrence of Premature Birth and Recurrent Acute Pulmonary Oedema in the Mother due to Cushing’s Syndrome: A Case Report - Anthony Bernard, Dorothy Maria A/p; Xin Yi, Ooi; Veerasamy, Hema Lata A/p; Long Bidin, Mohamed Badrulnizam; Chee Keong, See (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Presentation of Cushing’s syndrome during pregnancy is extremely rare. We report a 21-year-old female with Cushing’s syndrome diagnosed at 23 weeks of gestation and had recurrent acute pulmonary oedema during the antepartum and postpartum period. She delivered prematurely via emergency caesarean section at 28 weeks of gestation. This case highlights the rare occurrence of recurrent acute pulmonary oedema during pregnancy and consequential premature birth in a patient with adrenal Cushing’s. She was diagnosed with adrenal Cushing’s during the postpartum period based on unsuppressed serum cortisol after overnight and low-dose dexamethasone suppression test with a suppressed ACTH. CT scan of the adrenal glands revealed a right adrenal cortical adenoma. The risk of complications in infants and mothers who suffer from Cushing’s syndrome needs to be handled carefully. The diagnosis of Cushing’s syndrome in pregnant women often overlaps and is difficult to establish in early pregnancy.